Analisis Sistem Informasi Akuntansi pada Perusahaan Konstruksi - Pakpahan, Alryani Hidayat; Kanti, Annisa (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2023)
The Mandiri Internship was created with the aim of being a means for students to develop skills and apply knowledge in the world of professional work. The research was conducted at PT Nindya – Modern, KSO which is engaged in construction. The author's Independent internship is carried out in the company's accounting division by carrying out accounting activities in the form of checking proof of transactions in the cash and accounts payable division, studying the accounting system used by the company, making general journals for each transaction and participating in all routine activities outside the division. This research was conducted with a qualitative descriptive approach. The type of data collection used is documentation and interviews. The results of this analysis and research are that there are two accounting calculation methods in contracting companies, namely the Settlement Presentation Method and the Completed Contract Method. The limitation that occurred during the research was direct learning provided by the company so that the writer was required to take the initiative to find material to be used as research and submitted to the company.